“A Fruitful Development of the Discipline”: The University of Zadar Summer Schools, 2009-2016 - Gilliland, Anne J.; Willer, Mirna; Tomić, Marijana (Monografija u povodu 20 godina rada Odjela za informacijske znanosti u Zadru, 2025)
The paper first briefly introduces the roles of summer schools in recent decades and how they have advanced scholarship and doctoral education in the information fields. It then provides an overview of the doctoral programme in Knowledge Society and Information Transfer established in 2009 at the University of Zadar and explains how the Zadar summer schools were designed to support that new programme. It describes the scope of each summer school and discusses how the conceptualization, content, and participants of the summer schools evolved over the seven-year period during which they were organized and convened, summarizing the shifting research and professional themes and concerns to which they responded. The paper highlights the impact of the summer schools on two particular areas where scholars from the Department of Information Sciences have taken the lead nationally and internationally—the study of Glagolitism and the development of conceptual models and standards for the organization of information. It concludes with a brief discussion of the wider importance and impact of the conferences and summer schools in terms of scholarly production and doctoral education, international awareness, and professional networking.